Effects of copper sulphate administration to pregnant sheep on some mineral levels in blood sera of sheep and lambs, and birth weight of lambs - Çimtay, I; Sahin, T; Ölçücü, A; Aksoy, G (Scientific Technical Research Council Turkey, 2001)
In this study, copper sulphate was administered during the last period of pregnancy to sheep in the Sanhurfa region in which enzootic ataxia was encountered in the past. The objectives of this study were to search the effect of copper sulphate administration on some mineral levels (copper, zinc, iron, calcium and magnesium) in blood serum of pregnant sheep and their lambs, and birth weight of lambs. This study was performed on 35 pregnant sheep (control group: 15, experimental group: 20). In the experimental group, copper sulphate (2% solution) was administered orally at sixth and fourth weeks before birth at 2 and 1 g dosages, respectively. Blood samples of sheep were collected before copper administration, 4 times after copper administration and after birth. Furthermore, birth weights of lambs were determined just after birth and blood samples were collected after feeding colostrum. Copper administration caused significant increase on serum copper levels, but insignificant effects on serum zinc, iron, calcium and magnesium values in sheep and lambs. In addition, copper sulphate administration caused little increase on birth weights of lambs. Enzootic ataxia did not occur in both group of lambs, but mean serum copper values (59.66 +/- 2.35 mug/dl) in the control group were about 50 mug/dl which is considered as critical level for enzootic ataxia.
Gebe Koyunlara Bakir Sülfat Uygulamasinin Koyunlar ve Kuzularin Kan Serumlarindaki Bazi Mineral Düzeyleri ve Kuzularin Do?um A?irliklari Üzerine Etkileri
Keywords: blood serum; copper sulphate; minerals; sheep; lamb